2020
DOI: 10.14430/arctic71080
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Community Participation in Research: A Systematic Literature Review of Community-based and Participatory Research in Alaska

Abstract: Although concepts of “community” and “participation” have been heavily critiqued in the social sciences, they remain uncritically applied across disciplines, leading to problems that undermine both research and practice. Nevertheless, these approaches are advocated for, especially in Indigenous contexts. To assess the use of these concepts, we conducted a systematic literature review of community-based and participatory research in Alaska, USA, where social change has been rapid, having ramifications for socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…This is yet another part of the process in which clearer reporting on research design, in general, would be beneficial, as understanding who has defined the criteria for participation, as well as who may be actively or inadvertently excluded from the process, helps to identify the perspectives that are and are not represented in the resulting models (Hitomi and Loring, 2018). Others have similarly called for greater clarity in how participatory research more generally is reported (Mosurska and Ford, 2020).…”
Section: Participants and Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is yet another part of the process in which clearer reporting on research design, in general, would be beneficial, as understanding who has defined the criteria for participation, as well as who may be actively or inadvertently excluded from the process, helps to identify the perspectives that are and are not represented in the resulting models (Hitomi and Loring, 2018). Others have similarly called for greater clarity in how participatory research more generally is reported (Mosurska and Ford, 2020).…”
Section: Participants and Topicsmentioning
confidence: 99%
“…However, shifts towards participatory methodologies in the Arctic have been limited, fragmented, and at times tokenistic (Ford et al, 2016;Jones, Cunsolo and Harper, 2018;Carter et al, 2019), and while Indigenous Peoples are increasingly involved in research, the degree to which they are involved varies hugely (Brunet, Hickey and Humphries, 2014;6 Flynn and Ford, 2020;Mosurska and Ford, 2020). There are concerns that 'participation' has become a buzzword in research and policy discourse more broadly, that lacks true attempts to engage with transformative processes (Leal, 2007;Castleden, Morgan and Lamb, 2012), and can in fact lead to further marginalisation and reinforcement of existing power relations (Cornwall and Jewkes, 1995;Guta, Flicker and Roche, 2013;Janes, 2016;Berrang-Ford et al, 2018).…”
mentioning
confidence: 99%
“…Not all community-based interventions effectively address equity, and in some cases might contribute to inequity, particularly if community members are operationalized to reduce risk created at macro levels (Bankoff and Hilhorst, 2009;Clark-Ginsberg, 2021). Intra-community differences in power and resources that shape disaster risk and its management must also be navigated to avoid exacerbating intra-community inequity (Titz et al, 2018;Kapoor, 2002;Mosurska and Ford, 2020). Ultimately what is needed is what might be labeled a "high reliability approach" (Weick et al, 1999) to community-based disaster risk management, one where acute attention is paid to preventing disaster risk in an equitable and communitydriven manner.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other models of critical participatory research, participants should ensure that the terms of involvement for community members are transparent, mutually beneficial, and co‐constructed. Central to critical participatory and decolonial paradigms, broadly, is a reorientation of conventional power relationships, so that researchers ultimately answer to community (Mosurska & Ford, 2020; Patel, 2015). Within an EE, community members should have significant influence in deciding who owns, interprets, and communicates the data and the science—and to what ends.…”
Section: Research As An Equitable Exchangementioning
confidence: 99%